Quality - McCormick, Kate.; ScienceDirect eBooks (Oxford ; Boston : Butterworth Heinemann, 2002)
The Pharmaceutical Engineering Series is a comprehensive reference for the pharmaceutical professional covering all aspects from quality, documentation and validation through manufacturing processes to facility design and management. In 'Quality', Dr Kate McCormick provides the reader with comprehensive coverage of this vital subject, including the quality life cycle, management and cost of quality, GMP, auditing and inspections. This book with the others in the series will become a unique source of reference and educational material for the readership. Case studies and examples make the book of direct practical relevance to the professional in the pharmaceutical industry Find the answers you are looking for quickly and easily with clear indexing and referencing Reference to international standards and practice mean this book will be useful wherever you are working.
Quality Life Cycle; Quality Assurance and Quality Control; Quality Systems; Good Manufacturing Practice; Management of Quality; Cost of Quality; Qualified Person; Technology Transfer; Calibration; Auditing/Inspections; Pharmaceutical Microbiology; Quality Improvement Programmes; Quality Tools and Techniques; Glossary; Bibliography; Index.
Includes bibliographical references (pages 260-263) and index.
Print version record.
Elsevier
Keywords: Pharmaceutical technology; Pharmaceutical industry -- Quality control; MEDICAL -- Drug Guides; MEDICAL -- Pharmacology; MEDICAL -- Pharmacy; MEDICAL -- Nursing -- Pharmacology; Pharmaceutical industry -- Quality control; Pharmaceutical technology; Drug Industry -- standards; Electronic books